Supporting Practices to Break Chinese International Students’ Language Barriers: The First Step to Facilitate Their Social Adjustment - Ma, Junqian (Journal of International Students, 2020)
Due to the significant growth in Chinese students pursuing education abroad, there is an increasing trend for researchers to study Chinese international students’ challenges, especially the challenges in social adjustment. However, only a few studies intend to design activities or supporting practices to solve these challenges. This study, drawing upon cultural-historical theory and community psychology, provided four activities to break Chinese international students’ language barriers and facilitate their social adjustment. By conducting four trials, this study found that Chinese international students realize their English capabilities, become actively engaged in interactions, and experience positive emotions when positioned in practices that (a) provide structural guidance and active mobilization, (b) involve shared intersubjectivity and contradictions, and (c) offer support within their zone of proximal development.